Changes in Color and Physiological Components of The Postharvest Mango (Mangifera indica L.) Influenced by Different Levels of GA3 - Md. Khairul Islam; A. K. M. Rafiul Islam; M. A. R. Sarkar; M. Z. H. Khan; Shabiha Yeasmin (Graduate Program of Syiah Kuala University, 2013)
Abstract - This experiment consisted of two popular mango varieties in Bangladesh (viz., Langra and Khirshapat) and four different levels of Gibberellic acid (GA3) solution, namely control, 100, 200 and 400 ppm. The two factors experiment was assigned in randomized complete block design with tree replicates. Data obtained from various biochemical analyses in terms of physicochemical properties and shelf life of postharvest mango, were recorded and statistically analyzed for comparison among the mean values using DMRT and LSD. The results of the experiments exhibited that only the single effect of varieties was found to be significant in most of the parameters studied. Variety the Langra performed better in accumulating higher quantity of dry matter, ash, vitamin c content in all four experiments over Khirshapat. On the other hand, the Khirshapat showed better performance in achieving higher quantity of moisture, progressively lost physiological weight as well as extended shelf life and delayed skin color changes than Langra at all the storage duration. Keywords: Postharvest mango; Gibberellic acid; physiological components.